Museum of Folk Architecture / Open-air Museum next to the Ľubovňa Castle - Pavelčíková, Monika (Zbiór Wiadomości do Antropologii Muzealnej, 2020)
The goal of the construction of the Museum of Folk Architecture in Stara Lubovna was to document the material and spiritual culture of Slovaks, Spis Germans, Ruthenians, Gorals, Jews and Roma who lived here side by side for centuries and created cultural values of this region. The dominant feature of the exhibition is a national cultural monument - the Byzantine Rite Catholic Church of Matysova from 1833. Houses from the period (1900-1935) with furnished interiors show the way of life, daily activities, celebrations of important annual and family holidays. Agricultural and industrial buildings showcase exhibits related to their original use. During the summer season the museum complex holds events presenting customs, traditional activities, crafts and folklore. Thanks to its location right next to the medieval Lubovna Castle and unobstructed view of the High Tatras, the exposition presents a unique site in Slovakia.